FRI0003 Quality of Life and Economic Benefits of Remission/Low Disease Activity in Patients with Rheumatoid Arthritis in Clinical Practice Setting. (10th June 2014) - Alemao, E.; Joo, S.; Kawabata, H.; Al, M.; Allison, P.; Rutten-van Molken, M.; Frits, M.; Iannaccone, C.; Shadick, N.; Weinblatt, M.E.
Abstract : Background: Recent studies, primarily in clinical trial settings, have suggested that attaining remission/low disease activity (LDA) in patients with early-stage RA contributes to improved clinical outcomes. Objectives: Evaluate the associations between achievement of RA remission/LDA in clinical practice, as defined by Simplified Disease Activity Index (SDAI) <3.3, Clinical Disease Activity Index (CDAI) <2.8 and Disease Activity Score (DAS)28 (C-reactive protein; CRP) <2.6, and quality of life (QoL) measured by EQ5D and utilization of durable medical equipment (DME) and hospitalizations. Methods: Patients enrolled in the Brigham and Women's Hospital Rheumatoid Arthritis Sequential Study (BRASS) Registry, established in 2003, were analysed to address the study objective. The BRASS Registry comprises mostly patients with established RA who were evaluated semi-annually on multiple clinical patient-reported outcomes and resource utilization parameters. The current analysis is based on the first 5 years of patient follow-up in BRASS. All independent variables including disease activity (SDAI, CDAI, DAS28-CRP) were measured prior to the outcomes. To control for intra-class correlation of the panel data in BRASS, mixed models were used to estimate the fixed effects on the outcomes, and the generalized estimating equations (GEE) method was utilized for bivariate outcomes, DME use and hospitalizations. Variables for the fixed effects included baseline demographics, co-morbidities, family history of disease, duration of RA disease, joint replacement, disease activity and seropositivity. Results: A total of 1297 BRASS patients (82.3% female) were included. The mean (standard deviation [SD]) age of the study sample was 56.6 (14.1) years, with a mean (SD) duration of symptoms of 15.3 (13.0) years. Most (71.0%) patients were seropositive; 10.3% (n=134) and 7.0% (n=91) were in remission based on CDAI and SDAI criteria at baseline, respectively. A majority (95%) of patients were exposed to DMARDs and 45% of these were exposed to biologic DMARDs. After controlling for baseline covariates in the mixed models, improvements in EQ5D, DME use and hospitalizations were significantly associated with the attainment of remission/LDA versus moderate and severe disease activity (MDA and SDA, respectively), as defined by SDAI, CDAI, and DAS (see Table). Conclusions: Attainment of remission or low disease activity in patients with RA in clinical practice is associated with improvement in quality of life, reduced durable medical equipment use and reduced hospitalizations. Disclosure of Interest: E. Alemao Shareholder of: BMS, Employee of: BMS, S. Joo Shareholder of: BMS, Employee of: BMS, H. Kawabata Employee of: BMS, M. Al: None declared, P. Allison: None declared, M. Rutten-van Molken: None declared, M. Frits: None declared, C. Iannaccone: None declared, N. Shadick Grant/research support: ABBVIE, AMGEN, Genentech, M. Weinblatt Grant/research support: BMS, Crescendo Bioscience, UCB, Consultant for: BMS, Crescendo Bioscience, UCB, Abbvie, Roche, Janssen DOI: 10.1136/annrheumdis-2014-eular.1897